The Impact of Implementing SIA and Internal Controls on the Quality of Financial Statements at the PDAM Bireuen Office - Ima Waddah; Riska Fazira (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the effect of accounting information systems and internal control on the quality of financial statements at PDAM Krueng Peusangan, Bireuen Regency. The research uses a quantitative approach with an associative method. The population consists of 104 employees, while 73 respondents were selected using purposive sampling based on criteria of employees directly involved in the preparation, recording, and reporting of financial statements. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. The regression analysis results indicate that the accounting information system (X₁) has a positive and significant effect on the quality of financial statements, with a significance value of 0.000 < 0.05. The internal control variable (X₂) also has a positive and significant effect with a significance value of 0.000 < 0.05. Simultaneously, both variables significantly influence the quality of financial statements with a determination coefficient (R²) of 0.569. Thus, the better the implementation of the accounting information system and internal control, the higher the quality of financial statements produced by PDAM Krueng Peusangan.